تقويم إمكانية بناء خريطة المعرفة في جامعة تشرين - ديب, كندة; مرهج, ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدّراسة لتحديد مدى إمكانية جامعة تشرين بناء خريطة المعرفة وذلك من خلال إظهار مقوّمات البنية التحتية والبشرية والإدارية اللازمة، واعتمد الباحث على منهج المسح، وقام بتوزيع الاستبيان على 303 فرد من العاملين في الإدارة المركزية في جامعة تشرين، وكانت النتيجة الرئيسة الأهمّ في الدّراسة هي افتقار الجامعة للمقومات اللازمة (التحتية، والبشرية، والإدارية)، وعدم اعتمادها على نظم معلومات محاسبية وإدارية وبشرية تُسهل إمكانية الوصول السريع للبيانات والمعلومات، ثم تمّ عرض بعض التوصيات لضرورة حاجة الجامعة للمقوّمات اللازمة لبناء خريطة المعرفة، والتي أهمها: ضرورة العمل على تحديث قواعد البيانات باستمرار، والقيام بالإجراءات الإدارية والقانونية اللازمة لعملية التطوير الإلكتروني. This study aimed to evaluate the possibility to make knowledge map in Tishreen University through showing the administrative and human infrastructure. The researcher depended on the survey method where he distributed the questionnaire on 303 individuals of central administration in Tishreen University. The outcome was lack in the administrative and human infrastructure in the university, as it does not depend on accounting, administrative and human information systems that make easy and quick access to data and information. The researcher presented some of the recommendations including the need to work on a plan to make knowledge map by modernization of databases and to take the administrative and legal measures, which are necessary for electronic development.